Self- versus clinician-collected swabs in anal cancer screening: A clinical trial - Clare E. F. Dyer; Fengyi Jin; Jennifer M. Roberts; I. Mary Poynten; Annabelle Farnsworth; Leon P. McNally; Philip H. Cunningham; Andrew E. Grulich; Richard J. Hillman (PLoS ONE, 2025)
Background Risk of anal cancer is high in certain populations and screening involves collection of anal swabs for HPV DNA and/or cytology testing. However, barriers exist, such as the need for an intimate examination, and stigma around HIV status, sexual orientation, and sexual practices. Self-collected anal swabs (SCA) are a proposed alternative to clinician-collected swabs (CCA) to overcome these barriers. Methods Participants were order-randomised to undergo SCA or CCA first, with a second swab taken immediately afterwards. Sample adequacy was assessed for HPV DNA and cytology testing. CCA was used as the gold standard to calculate sensitivity and specificity of SCA for cytology and HPV results. Acceptability of swab collection was assessed following the procedure. Results There was no significant difference in sample validity for HPV DNA testing between SCA and CCA (p = 0.564). Concordance was >90% for detection of any HR-HPV and HPV16. There was no significant difference in cellular adequacy for cytological testing between SCA and CCA, (p = 0.162). Concordance for cytologic prediction was 88.2% for any cytologic abnormality. Almost half (48.5%) of participants expressed no preference for SCA versus CCA; 15.2% preferred SCA and 35.4% CCA. Conclusions SCA may be an acceptable and feasible alternative to CCA for detecting HPV and cytological abnormalities in a clinic population.